2018
DOI: 10.1002/cam4.1740
|View full text |Cite
|
Sign up to set email alerts
|

Transcultural adaptation and validation of the Persian version of the breast cancer awareness measure (BCAM) questionnaire

Abstract: Background/objectiveEnhancing awareness level about breast cancer is a pivotal strategy for reducing breast cancer burden. There is no fully validated Persian instrument for evaluating breast cancer awareness. This study aimed at investigating the validity and reliability of the Persian version of the Breast Cancer Awareness Measure (BCAM) questionnaire.MethodsThis methodological cross‐sectional study was conducted among 1078 Persian language women (including 965 general women and 113 medical/clinical experts)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 39 publications
2
21
1
Order By: Relevance
“…The internal reliability of the B-CAM-M was measured by Cronbach's alpha, and the findings suggested that there was high internal consistency between the items regarding knowledge about breast cancer symptoms (.83). This finding is in keeping with previous translation and validation studies of B-CAM in Arabic (Cronbach's alpha: .89), and Persian languages (Cronbach's alpha: .88) (Al-Khasawneh et al, 2016;Heidari and Feizi, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The internal reliability of the B-CAM-M was measured by Cronbach's alpha, and the findings suggested that there was high internal consistency between the items regarding knowledge about breast cancer symptoms (.83). This finding is in keeping with previous translation and validation studies of B-CAM in Arabic (Cronbach's alpha: .89), and Persian languages (Cronbach's alpha: .88) (Al-Khasawneh et al, 2016;Heidari and Feizi, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Some items from the domains of symptoms, risk factors and barriers had ICC values lower than 0.4 and discrepancies mainly occurred with respect to participants' knowledge and barriers for health care seeking. In comparison, a higher ICC value of 0.84 was reported for warning signs in the Persian version (Heidari and Feizi, 2018). A possible explanation for the lower ICC value might be related to the fact that although participants were not informed that they would be asked the same questions, some participants may have searched for information about breast cancer from the media and websites due to their interest and curiosity being stimulated by the first interview.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…More speci cally, these data composed of age, the rst menstrual age, age at rst childbirth, family history of breast cancer in rstdegree female relatives (mother, daughters, and sisters), history of taking a biopsy of the breast, number of biopsies, presence of dysplasia in the biopsy, educational level, marital status and occupation. We also used the Persian version of the breast cancer awareness measure (BCAM) questionnaire 25 . This scale originally developed by UK cancer center and validated speci c to BC awareness 26 .…”
Section: Data and Instrumentsmentioning
confidence: 99%
“…This scale originally developed by UK cancer center and validated speci c to BC awareness 26 . The Persian version of this scale was investigated by Heidari and Feizi 25 that showed a high test-retest reliability (ICC=0.84) and internal consistency (Cronbach's alpha=0.88). This scale composed of the knowledge of women in breast cancer risk factors and the sign and symptoms of breast cancer that included 14 items of multiplechoice scale to measure the awareness of risk factors and 8-item scale to assess the signs and symptoms with binary response.…”
Section: Data and Instrumentsmentioning
confidence: 99%